Comprasion of physical activity levels of working women and housewives according to some variables - Yavuz Yasul; Faruk Akcinar; Nuray Yigiter; Muhammet Enes Yasul (ROL Spor Bilimleri Dergisi)
This study aimed to examine the changes in physical activity levels of women according to some variables. Housewives (HW) and working women (WW) in certain institutions in Malatya voluntarily participated in the study. The volunteering participants were divided into two groups, WW (N=175) and HW (N=175), based on employment status. The International Physical Activity Questionnaire (IPAQ) short form was used to determine the physical activity levels of the participants in the study. According to the data obtained in the study, it was seen that the metabolic equivalent of task (MET) of the research group did not differ according to age, body mass index (BMI) and merital status, however the working status of the women affected their MET scores and the HW’s had a higher physical activity level than WW. It was seen that the inactive lifestyle habits of the working women in the research group affected their physical activity levels and they were not very active in the living areas left behind from the business life.